PENYIDIKAN TERHADAP PENYEDIA JASA PROSTITUSI MELALUI MEDIA INTERNET DI WILAYAH HUKUM POLISI DAERAH METRO JAYA - Putri Widjayanti; Mexasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
During the last five years range (2009-2014) there were four cases of prostitution services provider via the Internet which handled by the Polda metro jaya. In 2009 the AT suspect who manages the website with the domain name www.wanita18theclub.com. In December 2010, the Jakarta Police succeed to capture VL and WD that manages facebook account (kine kekasih gelapku) and www.bluefame.com website. In 2012 succeed to catch RW carriers website, NA-pimp and HD-field operations that manage the website with the domain name www.krucil.net, www.bintangmawar.net, www.semprot.net. They (RW carriers website, NA-pimp and HD-field operations). In March 2014, SL SY and the US suspect was captured by managing facebook account Andi Hotel Room.Investigation on prostitution services provider via the Internet is done by cyber part of polda metro jaya's TNCC unit is to track the whereabouts of offenders by tracing the Internet Protocol address (